Fulvic acid-like substance and its characteristics, an innovative waste recycling material from pulp black liquor. (10th January 2020) - Wang, Zhonghua; Shen, Tianlin; Yang, Yuechao; Gao, Bin; Wan, Yongshan; Li, Yuncong C.; Yao, Yuanyuan; Liu, Lu; Tang, Yafu; Xie, Jiazhuo; Ding, Fangjun; Chen, Jianqiu
Abstract: The pulp black liquor accounts for about 90 percent of pollution of the whole paper and pulp industry. The clean production technology of extracting useful bio-based substances from pulp black liquor can increase wastewater utilization and benefit the environment. This paper examines chemical characteristics and biological activities of fulvic acid-like substance extracted from leonardite (FA1), which serves as the benchmark, and from pulp black liquor (FA2). Instrumental analyses with Fourier transform infrared (FT-IR) spectroscopy, 13 C-nuclear magnetic resonance ( 13 C-NMR) spectroscopy and 1 H-nuclear magnetic resonance ( 1 H-NMR) spectroscopy indicated that FA1 and FA2 shared common functional groups existed in typical fulvic acid. A series of rice seed germination bioassays proved that FA2 had the same growth promotion function as FA1. The optimal concentration for water absorption and seed germination was 5 mg/L for FA1 and 60 mg/L for FA2. FA1 and FA2 treatments also increased the activity of α-amylase under the action of hydrolytic enzymes and promoted root development by increasing cell size and cell division. The study implied that pulp black liquor can be used for bio-renewable and eco-friendly production of fulvic acid for wide applications in agriculture. Graphical abstract: Image 108448 Highlights: Eco-friendly and bio-renewable FA-like substance was extracted from black liquor. FA-like substance from black liquor had similar functional groups with typical FA. Fulvic acid from black liquor enhanced rice seed germination and roots development. Fulvic acid from black liquor can be used as a functional fertilizer synergist. A potential strategy will be opened for wastewater reutilization in pulp industries.